2016
DOI: 10.1038/srep38623
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation for further conversion: from raw corn stover to lactic acid

Abstract: Fractionation is considered to be one promising strategy to utilize raw biomass to its fullest and produce chemicals with high selectivity. Herein, ethanol/H2O (1/1, v/v) co-solvent with 0.050 M oxalic acid is used to simultaneously fractionate 88.0 wt% of hemicellulose and 89.2 wt% of lignin in corn stover, while cellulose is not obviously degraded. H2O dissolves hemicellulose, G unit and those with β-O-4 linkage of lignin; whereas ethanol extracts G and S units as well as the skeleton with β-5 and β-β linkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 50 publications
(60 reference statements)
1
26
0
Order By: Relevance
“…Therefore, an appropriate pretreatment should be employed to remove the lignin and hemicellulose from the substrate, making the structure looser, in order to increase the accessibility of the cellulase to cellulose. The biomass pretreatment was performed by a novel method by He et al [ 50 ]. The bamboo was put in a 200 mL stainless steel autoclave equipped with a magnetic stirring device and a temperature controller.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, an appropriate pretreatment should be employed to remove the lignin and hemicellulose from the substrate, making the structure looser, in order to increase the accessibility of the cellulase to cellulose. The biomass pretreatment was performed by a novel method by He et al [ 50 ]. The bamboo was put in a 200 mL stainless steel autoclave equipped with a magnetic stirring device and a temperature controller.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of electron deficient Sn species, which helped in polarizing carbonyl bonds of sugars, was the key factor for improved performance of supported PtSn catalysts. He et al 305 proposed a potential strategy for the direct conversion of raw corn stover to lactic acid using ethanol/H 2 O and oxalic acid in the presence of MgO catalyst. Results revealed that ethanol/ H 2 O solvent system could efficiently fractionate corn stover into 88 wt% of hemicellulose and 89.2 wt% of lignin, while retaining a stable cellulose pulp.…”
Section: Valorization Of Lignocellulose Biomassmentioning
confidence: 99%
“…Pretreatment of biomass is important and can help improve product selectivity. Thus, strategies to enhance the selectivity have been developed, for example, liquid ammonia for lignin solubilization, ethanol/H 2 O with acid for hemicellulose hydrolysis, and NaOH/urea for cellulose dissolution . The combination of pretreatment and pyrolysis might provide better methods for biomass conversion.…”
Section: Resultsmentioning
confidence: 99%